Effects of the Commercial Yogurt Starter on the pH, aw, TPC, TotalBacteria of Lactic Acid, Yeast Mold Numbers and Organoleptic inFermented Sausages - Agus Susilo; Aris Sri Widati; Herly Evanuarini; Mulia Winirsya Apriliyani; Premy Puspitawati Rahayu; Dewi Septi Ayuning Tyas; Raihan Rafly; Ananda Diah Pramudita (Jurnal Ilmu-Ilmu Peternakan)
Yogurt culture has never been used as a probiotic to produce fermented sausages. The microorganisms that make up the starter culture play a role in the release of bioactive peptides during sausage production. This research aimed to determine the effect of yogurt starters on chicken meat and the best percentage of fermented chicken sausage made with yogurt starters as lactic acid bacteria. The variables used are pH, water activity, total plate number, total LAB, yeast mold number, and organoleptic tests. The research method was experimental via a completely randomized design (CRD) with 4 treatments and 3 replications. The yogurt starter addition amounts used were 0%, 1%, 2%, and 3%. The data were analyzed via analysis of variance (ANOVA). If there is a significant effect, it will be tested via Duncan's multiple range test (DMRT). The results revealed that there was a highly significant difference (P<0.01) in pH and that there was a significant difference (P<0.05) in total lactic acid bacteria (LAB) and organoleptic aroma, taste and texture. Moreover, there were no significant differences (P>0.05) in water activity, total plate number, yeast mold number, or organoleptic tests on the color of fermented sausage